mplementation of Emergency Training to Improve the Safety of Crew at MV.Urmila - Dedtri Anwar; Iksan Saifudin; Aliong Silalahi; Jaya Alamsyah; Frisca Mareyta Pongoh (Meteor STIP Marunda, 2025)
The safety of shipping at sea is also very important in the maritime world. Disturbances when the ship sails are mostly due to natural factors, but it is possible that it can be caused by factors from the ship itself (engine damage). Any disruption at the time of sailing is an emergency as it will slow the ship down to arrive on time. Prevention of emergencies that have been determined in accordance with SOLAS and SOPs is very important. Although rules and conditions have been set that must be implemented by ships with emergency training procedures and procedures, it is evident that in reality there are still problems or lack of implementation of emergency exercises on board. to discuss how safety exercises on ships are implemented based on the provisions of SOLAS and SOP on board with the aim that in the implementation of the exercise can be useful during the actual incident, so that the souls of the crew, ship and the environment can be saved. But in fact, emergency exercises are not implemented optimally. The research approach used is qualitative descriptive through observation, interview, and documentation data collection techniques. The results of this study show that emergency training does not run optimally because there are several factors, namely, the non-routine of emergency exercises in accordance with SOLAS and SOPs on board, the unavailability of spare safety equipment during emergency exercises, and the lack of discipline of the crew when carrying out emergency exercises.